EZH2 expression in colorectal carcinoma: an evaluation of clinicopathological and prognostic value - Diren Vuslat Cagatay; Mecdi Gurhan Balci; Gizem Issin; Fatih Demir (Discover Oncology)
Abstract Background Enhancer of zeste homolog 2 (EZH2), the catalytic subunit of Polycomb Repressive Complex 2, catalyzes trimethylation of histone H3 lysine 27 and has been implicated in tumor progression. Aim Our study aims to assess the relationship between EZH2 expression and clinicopathologic data, and survival in colorectal carcinomas (CRC). Materials and methods EZH2 immunohistochemistry was performed on tumor blocks from 124 CRC patients. Based on H-scores, cases were stratified into low- and high-expression groups. EZH2 status was correlated with demographic, clinical, and pathologic features, and overall survival was analyzed with the Kaplan–Meier method and log-rank test. Results A total of 124 cases of CRC; 12 (9.7%) cases were classified as low EZH2 expression, and 112 (90.3%) cases were classified as high EZH2 expression. A significant association was found between EZH2 expression and microsatellite stability. High EZH2 expression was significantly enriched in microsatellite-stable tumors (p = 0.007) and in left-sided lesions (p = 0.049). No significant associations were detected with sex, stage, grade, lymph-node status, or vascular invasion. Kaplan–Meier analysis revealed no difference in overall survival between low- and high-EZH2 groups (log-rank p = 0.47; hazard ratio = 1.13, 95% CI 0.45–2.85). EZH2 staining was uniformly strong in normal mucosa and adenomas, mirroring the high expression observed in most CRCs. Conclusions EZH2 is highly expressed across the normal-adenoma-carcinoma sequence and, in our cohort, was not linked to overall survival or to most clinicopathologic parameters in CRC. The lower expression observed in a subset of MSI-H tumors warrants further investigation; present evidence remains insufficient to establish EZH2 as an independent prognostic biomarker.